2022
DOI: 10.3389/fpls.2022.1035233
|View full text |Cite
|
Sign up to set email alerts
|

MbHY5-MbYSL7 mediates chlorophyll synthesis and iron transport under iron deficiency in Malus baccata

Abstract: Iron (Fe) plays an important role in cellular respiration and catalytic reactions of metalloproteins in plants and animals. Plants maintain iron homeostasis through absorption, translocation, storage, and compartmentalization of iron via a cooperative regulative network. Here, we showed different physiological characteristics in the leaves and roots of Malus baccata under Fe sufficiency and Fe deficiency conditions and propose that MbHY5 (elongated hypocotyl 5), an important transcription factor for its functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The transgenic calli also exhibited the same trend (Figure 6B). Most of the Fe in plant species is in the leaves, so the accumulation of Fe in plants can be judged by the chlorophyll level [42]. In this experiment, it was observed that under Fe-deficiency conditions, the chlorophyll content of transgenic tobacco leaves was significantly higher compared to WT tobacco.…”
Section: Discussionmentioning
confidence: 71%
“…The transgenic calli also exhibited the same trend (Figure 6B). Most of the Fe in plant species is in the leaves, so the accumulation of Fe in plants can be judged by the chlorophyll level [42]. In this experiment, it was observed that under Fe-deficiency conditions, the chlorophyll content of transgenic tobacco leaves was significantly higher compared to WT tobacco.…”
Section: Discussionmentioning
confidence: 71%
“…Grapevine rootstocks in our experiment affected the relation between Fe content in young leaves and their total chlorophyll content. Although Fe is essential for chlorophyll biosynthesis [ 96 ], the observed phenotype and the changes in chlorophyll could reflect the Fe requirement for nitrate assimilation, as recently proposed [ 77 ]. The chlorophyll content of plants under treatment N1A1/-Fe were less affected compared to plants supplied with nitrate as the sole N source (3309 C: mean values: N1A0/-Fe = 2.75 ± 0.38, N1A1/-Fe = 5.86 ± 0.78; Welch´s F(1, 5.808) = 12.907, p = 0.012; Fercal: mean values: N1A0/-Fe = 3.23 ± 0.35, N1A1/-Fe = 6.01 ± 0.78; Welch´s F(1, 5.560) = 10.480, p = 0.020).…”
Section: Discussionmentioning
confidence: 88%
“…The activation of SlFER expression leads to the activation of downstream Fe uptake genes including FERRIC REDUCTASE OXIDASE ( SlFRO1 ), IRON‐REGULATED TRANSPORTER ( SlIRT1 ), and NATURAL RESISTANCE‐ASSOCIATED MACROPHAGE PROTEINS ( SlNRAMP1 ). In apple ( Malus baccata ), it has been discovered that the MbHY5 positively regulates the expression of MbYSL7 under Fe deficiency, which leads to the alleviation of Fe deficiency caused chlorosis and promotion of Fe transport (Sun et al ., 2022). In Arabidopsis, it has been demonstrated that HY5 function is essential for seedling growth under Fe deficiency, as the hy5 mutant displayed higher reduction in root growth and chlorophyll content as compared to WT under Fe deficiency.…”
Section: Ironmentioning
confidence: 99%
“…Similarly, in Arabidopsis, HY5 has been shown to positively regulate Fe uptake by inducing the expression of genes involved in Fe uptake (Mankotia et al ., 2023). In apple, it has been shown that MbHY5 plays a crucial role in regulating Fe transport and chlorophyll synthesis (Sun et al ., 2022). These findings collectively imply that HY5 functions are conserved across plant species and are essential for coordinating the nutrient uptake and assimilation in response to light.…”
Section: Hy5 Role In Multi‐nutrient Uptake and Utilization Is Conserv...mentioning
confidence: 99%